2007
DOI: 10.1108/07378830710840473
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of web‐based library databases: the vendors' perspectives in 2007

Abstract: PurposeWeb‐based research databases are common in today's libraries, but most librarians lack the ability to evaluate them for accessibility for persons with disabilities. Consequently, they rely upon resource providers to develop products that are ADA and Section 508 compliant. Are database vendors stepping up to the plate? As a follow‐up to a study reported in 2003, the purpose of this paper is to investigate accessibility of online databases from database vendors' perspectives.Design/methodology/approachRes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…The three databases selected represented three different vendors (ProQuest, CSA and Gale, respectively) of electronic resources commonly used by students at both universities. The vendors' perspectives study by Byerley et al (2007) indicated that EBSCO was a proactive vendor in terms of product accessibility and therefore was not selected for this study. The order of databases searched alternated with each participant.…”
Section: Methodsmentioning
confidence: 99%
“…The three databases selected represented three different vendors (ProQuest, CSA and Gale, respectively) of electronic resources commonly used by students at both universities. The vendors' perspectives study by Byerley et al (2007) indicated that EBSCO was a proactive vendor in terms of product accessibility and therefore was not selected for this study. The order of databases searched alternated with each participant.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies investigate the accessibility and usability of these online resources for people using assistive technologies. All of these indicate that while most indexes and databases are now largely compliant with common accessibility standards and permit the performance of common search tasks, their actual user friendliness for people with disabilities tends to be low (Byerley, Chambers, & Thohira, 2007;Riley, 2002;Stewart et al, 2006). Other studies build on the accessibility evaluation process and provide best practices for enhancing access to electronic resources (Tatomir & Durance, 2010;Tatomir & Tatomir, 2012).…”
Section: Literature Reviewmentioning
confidence: 97%
“…A 2007 survey of corporations found that a vast majority do not conduct accessibility tests of their sites with users with disabilities, while those with accessible sites rarely promote such accessibility in marketing efforts [2]. Collectively, the findings from all of these studies demonstrate that most corporations have not "sufficiently recognized the importance of customers with disabilities to their business goals" [21].…”
Section: Introductionmentioning
confidence: 99%